The Compatibility between the Religious and the Nihilistic Currents in Dostoevsky’s World - Sun, Haozhan (Labyrinth, 2021)
The goal of this essay is to show the compatibility between two currents in Dostoevsky's world, namely, the religious and the nihilistic. Based on Nietzsche's theory of nihilism and Deleuze's interpretation of Nietzsche, I introduce a dynamic model – reactive nihilism – a destructive force that annihilates fading values to clear the way for the advent of a new value. Through the textual analysis, primarily focusing on the religious dimension presented by saintly characters and biblical intertextuality in The Brothers Karamazov, this essay argues that Dostoevsky's two trends do not conflict at all, but express in a common dynamic model, that is reactive nihilism.